The Impact of Informal Digital Learning of English (IDLE) on EFL Learners’ Engagement: Mediating Roles of Flow, Online Self-Efficacy, and Behavioral Intention - Fang Fang; Yaru Meng; Lingjie Tang; Yu Cui (Behavioral Sciences)
In the evolving landscape of online language learning, informal digital learning of English (IDLE) plays a crucial role, particularly among English as a foreign language (EFL) learners. Previous research has investigated the direct impact of IDLE on EFL learners’ engagement. However, little attention has been given to the underlying mechanisms that drive this relationship. To address the gap, this study examined the mediating roles of flow, online self-efficacy, and behavioral intention in the relationship between IDLE and EFL learners’ engagement, with survey data collected from 1194 Chinese EFL learners. Findings reveal that flow, online self-efficacy, and behavioral intention serve as key mediators between IDLE and EFL learners’ engagement in the digital setting. These results offer deeper insights into how informal digital learning influences EFL learners’ engagement in digital contexts, providing valuable implications for both educational theory and digital learning practices.